PENERAPAN MODEL PROJECT BASED LEANRNING DALAM PERSPEKTIF ONTOLOGI DAN EPISTEMOLOGI FILSAFAT PENDIDIKAN MATEMATIKA - THITRA PADMA RANI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2023)
The purpose of this study is to describe the Project Based Learning model in the perspective of the philosophy of mathematics education in ontology and epistemology. This article is reviewed using library research, examining the Project Based Learning model and the philosophy of mathematics education in terms of ontology and epistemology. The results of the study found that the Project Based Learning model begins with providing problems which are then sought for solutions through the given project. This is in accordance with the ontology of the philosophy of science, namely empiricism and logicalism. The Project Based Learning model also guides students to develop collaborative skills, critical thinking skills and problem solving abilities. Epistemologically according to the flow of constructivism that the process of constructing meaning from one experience is then discussed through a combination of experience that has been owned with new experience to produce new knowledge. ABSTRAKTujuan dari kajian ini untuk mendeskripsikan model Project Based Learning dalam perspektif filsafat pendidikan matematika secara ontology dan epistemlogi. Artikel ini dikaji menggunaka library research, mengkaji model Project Based Learning dan fisafat pendidikan matematika secara ontology dan epistemology. Hasil kajian menemukan bahwa model Project Based Learning diawali dengan memberikan permasalahan yang kemudian dicari penyelesaiaanya melauli proyek yang diberikan. Hal ini sesuai dengan ontology filsafat ilmu yaitu aliran empirisme dan logikalisme. Model Project Based Learning juga membimbing peserta didik untuk mengembangkan keterampilan kolaboratif, kemampuan berfikir kritis dan kemampuan pemecahan masalah. Secara epistemology sesuai aliran kontruksivisme bahwa proses mengkontruksi artinya dari satu pengelaman kemudian didiskusikan melalui perpaduan pengelaman yang telah dimiliki dengan pengalaman baru menghasilkan sebuah pengetahuan baru.